A Tentative Framework for the Philosophy of the Canadian Labour Movement - Kovacs, Aranka (Relations industrielles / Industrial Relations, 1965)
The philosophy of the Canadian labour movement is examined in the light of the three stages which characterize the pattern of union growth. The author shows how youthful years idealism gave way to a pragmatic philosophy over the last two decades.